2020
DOI: 10.1186/s12872-020-01570-6
|View full text |Cite
|
Sign up to set email alerts
|

Population attributable risk estimates of risk factors for contrast-induced acute kidney injury following coronary angiography: a cohort study

Abstract: Background: Contrast-induced acute kidney injury (CI-AKI) is a common complication with poor outcomes following coronary angiography (CAG) or percutaneous coronary intervention (PCI). However, no study has explored the population attributable risks (PARs) of the CI-AKI risk factors. Therefore, we aimed to identify the independent risk factors of CI-AKI and estimate their PARs. Methods: We analyzed 3450 consecutive patients undergoing CAG/PCI from a prospective cohort in Guangdong Provincial People's Hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
(34 reference statements)
1
8
1
Order By: Relevance
“…The studies meeting all the following criteria were included in this meta-analysis [ 1 ]: observational study [ 2 ]; explored the relationship between anemia and CI-AKI in patients who underwent coronary angiography with or without percutaneous coronary intervention (PCI); and [ 3 ] reported outcomes with the adjusted odds ratios (ORs) or relative risks (RRs) with 95% confidence intervals (CIs). If more than one studies enrolled the overlapping population, we chose the newly published study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies meeting all the following criteria were included in this meta-analysis [ 1 ]: observational study [ 2 ]; explored the relationship between anemia and CI-AKI in patients who underwent coronary angiography with or without percutaneous coronary intervention (PCI); and [ 3 ] reported outcomes with the adjusted odds ratios (ORs) or relative risks (RRs) with 95% confidence intervals (CIs). If more than one studies enrolled the overlapping population, we chose the newly published study.…”
Section: Methodsmentioning
confidence: 99%
“…Coronary angiography has been widely applied in the diagnosis and therapy of coronary artery disease (CAD) for several decades [ 1 ]. Unfortunately, many clinical studies reported that coronary angiography could significantly increase the risk of contrast-induced acute kidney injury (CI-AKI) [ 1 , 2 ]. The reported incidences of CI-AKI were distinct across different studies, ranging from 2% to 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with the Mehran score, the current nomogram has several strengths. First, our previous study showed that the CI-AKI definition of this study has higher population attributable risk (PAR) than that of the CI-AKI definition of the Mehran score, which means the current CI-AKI definition has better prognostic value [36]. Second, the current nomogram with only 4 variables was established for CHF patients specifically.…”
Section: Discussionmentioning
confidence: 86%
“…Mechanisms such as free oxygen radical damage, diuresis caused by contrast, increased urinary viscosity, infl ammation, direct toxicity, tubular toxicity, increased oxygen consumption and renal vasoconstriction are involved in the pathogenesis [5,6].…”
Section: Pathogenesismentioning
confidence: 99%
“…Renal disease history, diabetes and advanced age are the most common risk factors. However, chronic heart failure, hypertension, dehydration, nephrotoxins (aminoglycoside, nonsteroidal anti-infl ammatory, cyclosporine), anemia, periprocedural bleeding and female gender are other risk factors [5].…”
Section: Risk Factorsmentioning
confidence: 99%